Literature Review: Pengukuran Kesiapan Tenaga Kesehatan dalam Menerima Telehealth atau Telemedicine antara Negara Maju dan Negara Berkembang - Nadharuth Febrizhya Abigael; Ernawaty Ernawaty (Politeknik Kesehatan Tanjung Karang, 2020)
Telehealth and telemedicine become a necessity in health services amid technological advancements so that health services can reach the wider community to remote places. Implementing telehealth and telemedicine must be accompanied by the readiness of health workers to adapt to it. The purpose of this study is to determine the readiness of health workers in developed and developing countries and the barriers that affect the readiness of health workers. The research method is a literature review. Articles are chosen through google scholar, SAGE, JSTOR, and Science Direct with the keyword “e-health readiness”, “telehealth readiness”, and “telemedicine readiness”. From a total of 4783 articles, there were 56 articles selected based on abstracts and measurement targets and in the end, 18 articles were taken that were full text available for review. The most common dimensions to measure the readiness of healthcare on telehealth or telemedicine are core readiness, engagement readiness, and structural readiness. The implementation in a developed country is quite good based on core readiness and engagement readiness dimensions, but it needs more improvement in the structural readiness dimension, while in developing countries, there are already some countries that run it well but most are still constrained in infrastructure and resources financial. Overall, obstacles to running telehealth or telemedicine are also affected by the lack of available technological infrastructure in a country, lack of training of health workers, and lack of capacity building for health workers so that they are less able to adapt to telehealth and telemedicine.